Community Social Capacity Managing Community Forest In Banggai Regency, Central Sulawesi - Lawasi, Moh. Andika (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Studi Islam Sunan Doe, 2022)
This study aims to describe and evaluate the extent to which the social capacity of farming communities has changed in managing Community Forests (HKm) in Nambo Lempek Village, Banggai Regency, Central Sulawesi. The approach used is a qualitative descriptive method. Data collection techniques using the method of observation, interviews and documentation. The triangulation technique of checking the data's validity is used. The data analysis method used is data reduction, data presentation and conclusion. The results showed no real empowerment through efforts to increase community capacity in the process of empowering communities in the forest carried out by the state communities around the forest through the Community Forest program in Banggai Regency. There is a fragility in the social capacity of forest farming communities in managing HKm, marked by a decrease in community collective self-confidence, low intensity of collaboration, weak management institutions, and the inability to manage HKm independently.